Economics for investment decision makers micro, macro, and international economics - Piros, Christopher Dixon; Pinto, Jerald E. (Hoboken, N.J. Wiley, 2013)
The selection of fundamental topics in this book is comprehensive, with coverage of topics such as international trade, foreign exchange markets, and currency exchange rate forecasting reflects global perspectives of pressing investor importance.
PART II. Solutions: CHAPTER 1. Demand and Supply Analysis: Introduction -- CHAPTER 2. Demand and Supply Analysis: Consumer Demand -- CHAPTER 3. Demand and Supply Analysis: The Firm -- CHAPTER 4. The Firm and Market Structures -- CHAPTER 5. Aggregate Output, Prices, and Economic Growth -- CHAPTER 6. Understanding Business Cycles -- CHAPTER 7. Monetary and Fiscal Policy -- CHAPTER 8. International Trade and Capital Flows -- CHAPTER 9: Currency Exchange Rates -- CHAPTER 10: Currency Exchange Rates: Determination and Forecasting -- CHAPTER 11. Economic Growth and the Investment Decision -- CHAPTER 12. Economics of Regulation.
Includes bibliographical references and index.
Keywords: Supply and demand; Microeconomics; Macroeconomics; Investments; Electronic books